2011
DOI: 10.1029/2011jg001735
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence characteristics and sources of dissolved organic matter for stream water during storm events in a forested mid-Atlantic watershed

Abstract: [1] The concentrations and quality of dissolved organic matter (DOM) and their sources were studied for multiple storm events collected over a three-year period in a forested headwater (12 ha) catchment in the mid-Atlantic Piedmont region of the USA. DOM constituents were characterized using a suite of indices derived from ultraviolet absorbance and PARAFAC modeling of fluorescence excitation emission matrices. Runoff sources and hydrologic flow paths were identified using an end-member mixing model, stable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
150
4

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 172 publications
(167 citation statements)
references
References 57 publications
13
150
4
Order By: Relevance
“…The unsaturated zone in the present study contains a weathered clay layer (saprolite) where strong DOC sorption usually occurs (Jardine et al 1989;Kalbitz et al 2000). The relatively low concentrations of DOC in groundwater are consistent with pervious studies showing decreasing concentrations of DOC with soil depth (Pabich et al 2001;Goldscheider et al 2006;Inamdar et al 2011).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The unsaturated zone in the present study contains a weathered clay layer (saprolite) where strong DOC sorption usually occurs (Jardine et al 1989;Kalbitz et al 2000). The relatively low concentrations of DOC in groundwater are consistent with pervious studies showing decreasing concentrations of DOC with soil depth (Pabich et al 2001;Goldscheider et al 2006;Inamdar et al 2011).…”
Section: Discussionsupporting
confidence: 69%
“…The S 275-295 values in groundwater were significantly higher than those in surface waters (Shen et al Data are reported as the average ± standard deviation Biogeochemistry (2015) 122:61-78 73 2012b; this study), indicating the average molecular weight of DOM in groundwater is lower than that in surface water (Helms et al 2008). Microbial degradation and sorption onto minerals in the unsaturated zone are likely responsible for the removal of lignin and other components of chromophoric DOM (Kaiser et al 2004;Inamdar et al 2011;Ward et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses of the resultant influx of DOC and DON in the Archer Creek watershed during the growing season have shown close linkages with watershed wetness with notable increases in DOC during storms after dry antecedent periods (Inamdar et al, 2008;von Schiller et al, 2015). Studies of other lake/watersheds have found lower DOC concentrations under dry conditions (Schindler et al, 1997) with elevated DOC concentrations under wetter conditions (Hinton et al, 1997;Inamdar et al, 2011;Singh et al, 2014;Tranvik and Jansson, 2002). The increase in DOC concentrations in surface waters with increases in wetness of catchments has been attributed to the generation of flow paths through organic rich soil, including the forest floor (Inamdar et al, 2008), and Park et al (2003) also showed seasonal increases of DON due to soil microbial production from December 1996 to May 1996 in the lake inlet.…”
Section: Temporal Patterns Of Doc and Don Concentrations In Forested mentioning
confidence: 99%
“…All sediments were analyzed for % OC and N, stable isotopes of C and N ( 13 C and 15 N) using EAIRMS. In addition, solution extract of the sediment sources were also evaluated with fluorescence spectroscopy (see Johnson et al submitted, for a complete description) to produce fluorescence metrics like % protein-, humic-, and fulvic-like contents (Inamdar et al 2011). The aqueous extracted samples were also analyzed for total organic carbon (TOC) and total nitrogen (TN) on a Shimadzu TOC-L, TNM-L analyzer (Shimadzu, Colombia, MD).…”
Section: Site Descriptionmentioning
confidence: 99%
“…1) have been intensively studied Inamdar 2013, 2014;Inamdar et al 2011Inamdar et al , 2013Inamdar et al , 2015 and are located in the Piedmont physiographic province in Cecil County, Maryland. The watersheds drain into the Big Elk Creek which subsequently empties into the Chesapeake Bay.…”
Section: Site Descriptionmentioning
confidence: 99%